Performance assessment of Tsunami-HySEA model for NTHMP tsunami currents benchmarking. Field cases. - Macías-Sánchez, Jorge; Castro-Díaz, Manuel Jesús; Ortega-Acosta, Sergio; González-Vida, José Manuel (Elsevier, 2020)
Este trabajo evalúa el rendimiento del modelo Tsunami-HySEA en la simulación de corrientes inducidas por tsunamis mediante su aplicación a los benchmarks con datos de campo del NTHMP (2015). Se analizan dos casos reales del tsunami de Tohoku de 2011: el puerto de Hilo (Hawái) y el puerto de Tauranga (Nueva Zelanda). Los resultados numéricos, comparados con observaciones de elevación de la superficie libre y velocidades de corriente, muestran una alta capacidad del modelo para reproducir con precisión la dinámica del tsunami, validando su uso en estudios operativos de peligrosidad en puertos.

In this study, we present model results derived from the tsunami current benchmarking workshop held by the NTHMP (National Tsunami Hazard Mitigation Program) at Portland in February 2015 for the two benchmark problems dealing with field data. In this workshop, the Tsunami-HySEA model was used to perform the five numerical benchmarks proposed. The three benchmarks based on lab data are the subject of a companion paper (part I). The results and comparison with measured data for the two benchmarks dealing with field observations are described in the present paper, this includes: (1) Benchmark #2, impact of tsunami waves at Hilo Harbor, Hawaii, and (2) Benchmark #3, tsunami currents at Tauranga Harbor, New Zealand, both for data from the 2011 Tohoku event. We demonstrate that the Tsunami-HySEA model is able to accurately reproducing sea surface elevations and current velocities for both the local reduced benchmark problem as in the case of the complete scenario modeled from the source.
https://openpolicyfinder.jisc.ac.uk/id/publication/17105?from=single_hit
Keywords: Maremotos; Modelos matemáticos; Tsunami-HySEA; Corrientes de tsunami; Modelización numérica; Validación con datos de campo; NTHMP benchmarks; Tsunami de Tohoku 2011; Puertos costeros; Peligrosidad por tsunamis